Modes of exchange, metabolism and social formations: contributions from Kojin Karatani's framework to think about the spatial dimension - Costa, Bruno Moreira Riani [UNESP] (Univ Federal Espirito Santo, 2022)
Marxist philosopher and literary critic, Kojin Karatani is widely considered one of the most important Japanese theorists of our time. Some of his innovative perspectives began to be disseminated in Western academic debate as some of his works were translated into the English language. Within this framework, the arguments contained in his book The Structure of World History were highlighted, in which the author proposes re-readings of certain Marxian categories placed in perspective in an attempt to reinterpret universal history. His proposal to deal with modes of exchange and his recovery of the concept of metabolism to describe the relationship established between society and nature, for example, are among his contributions. In this sense, the present article intends to present in a summarized way some of the ideas contained in Karatani's theoretical scheme, seeking to point out how they could be mobilized to contribute to certain debates in geography.
Keywords: metabolism; modes of exchange; geography